Efektivitas Pengeluaran Pemerintah dalam Meningkatkan Pelayanan Publik di Era Digital - Ahmad Wahyudi Zein; Aliya Fayyaza; Isma Awaliyah Sipahutar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Digital transformation has become a central driver in reforming public services in Indonesia. However, the effectiveness of government expenditure in supporting this transition remains a critical issue. This study aims to examine the extent to which public spending contributes to the improvement of digital public service quality, efficiency, and accessibility. Using a quantitative approach with a descriptive-explanatory design, data were collected from ten regional governments through documentation and surveys. The results show a positive correlation between government spending on digitalization and service performance, although this relationship is also influenced by factors such as infrastructure readiness, human resource capacity, public participation, and inter-agency coordination. The findings emphasize the importance of sustainable budgeting and measurable monitoring in managing digital fiscal policies. The study recommends an integrated strategy combining fiscal planning, bureaucratic capacity-building, and public digital literacy to ensure inclusive and impactful digital service transformation.